MANAJEMAN PENERIMAAN PESERTA DIDIK BARU (PPDB) BERBASIS ONLINE DALAM UAPAYA PENINGKATAN MUTU LAYANAN PADA MTs MATLAUL ANWAR TANGGAMUS - Hidayah, Nur (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2023)
The development of Information Technology continues to show developments in each era. One of the information system media that is really needed today is a website-based information system. The information system for accepting new students at MTs Matlaul Anwar will use a website-based information system. The aim of implementing this online admission system is to simplify service and shorten the time for registering new student admissions. This website for online new student admissions can be used to manage student data, store it, and send it to the school admin in the form of a database or Excel sheet. The development method used in this research is the waterfall method. Online-based New Student Admission Management (PPDB) is a system designed to increase efficiency, transparency, and fairness in the process of admitting new students to educational institutions. The implementation of this system also aims to improve the quality of services to the community by utilizing information technology.